2018
DOI: 10.5747/ca.2018.v14.n3.a222
|View full text |Cite
|
Sign up to set email alerts
|

A GENOME-WIDE ANALYSIS OF THE GALACTINOL SYNTHASEGENE FAMILY IN BANANA (Musa acuminata)

Abstract: Galactinol synthase (GolS) is theenzyme that catalyzes the first step of the biosynthesis of the raffinose family oligosaccharides (RFOs), andisinvolved in manybiological processes in plants.In the present study, four putative GolSgenes were identified in the Musa acuminatagenome. We further characterized these MaGolSgenes in terms of protein length, molecular weight, theoretical isoelectric point and 3D protein structure. Genomic organization revealed that most MaGolSgenes have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…Subcellular localization predictions for ItlbGolS and ItfGolS suggest that diversity is found in the cell wall, chloroplast, cytoplasm, mitochondrion, peroxisome, cell membrane, and nucleus (Table Supplementary 1). As previously reported, some subcellular locations are in the same membrane tissue (Santos et al, 2011;Fan et al, 2017;Dolcimasculo et al, 2018).…”
Section: Resultssupporting
confidence: 75%
See 2 more Smart Citations
“…Subcellular localization predictions for ItlbGolS and ItfGolS suggest that diversity is found in the cell wall, chloroplast, cytoplasm, mitochondrion, peroxisome, cell membrane, and nucleus (Table Supplementary 1). As previously reported, some subcellular locations are in the same membrane tissue (Santos et al, 2011;Fan et al, 2017;Dolcimasculo et al, 2018).…”
Section: Resultssupporting
confidence: 75%
“…Based on this valuable information, it can be suggested that in sweet potato, this gene presents less diversity in its structure. In Musa acuminata, the exon/intron of the GolS genes shows three or four exons (Dolcimasculo et al, 2018). According to Figures 1 and 2, there may be a variation in the number of exons and introns in the ItlbGolS and ItfGolS genes, and we can also suggest that some genes are duplicated.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…Galactitol and raffinose synthase enzymes are critical for raffinose synthesis [ 5 ]. To date, there were a few reports regarding GolS and RFS genes in horticultural crops, such as cucumber [ 40 ], peas [ 41 ], apple [ 12 ], banana [ 42 ], tea [ 7 ] and grapevine [ 24 ]. Kiwifruit is an important horticultural crop with enriching in vitamin C [ 26 ].…”
Section: Discussionmentioning
confidence: 99%